Analisis Kesuksesan Website Pondok pesantren Al Kamal Kebumen Menggunakan Model DeLone & McLean - Fani Dwi Fikasari; Eko Setiawan; Asti Ratnasari; Yanuar Wicaksono (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2025)
The website of Pondok Pesantren Al-Kamal Kebumen serves as a medium for delivering information and providing pesantren services. However, its utilization remains suboptimal due to limited content updates, which has led to low visitor interest. Despite this, the website continues to make a positive contribution by expanding communication reach, facilitating information access, and enhancing transparency in pesantren activities. This study aims to evaluate the website's success level using the DeLone and McLean Model (2003), which includes six dimensions: system quality, information quality, service quality, use, user satisfaction, and net benefit. A descriptive quantitative method was employed through the distribution of a 4-point Likert scale questionnaire to 210 student respondents. The data were then analyzed using Structural Equation Modelling (SEM) based on Partial Least Square (PLS). The results show that out of nine hypotheses tested, six were accepted and three were rejected. Service quality and system quality significantly influence both use and user satisfaction. Use also has a significant effect on user satisfaction, while user satisfaction significantly affects net benefit. However, information quality does not significantly affect use or user satisfaction, and use does not significantly affect net benefit. Overall, the website's success level falls into the moderate category, with the R-square value for the net benefit variable at 42.5%. These findings indicate that a portion of the benefits perceived by users can be explained through the research model, although other external factors beyond the model also have an influence.